Uji Organoleptik Ikan Mujair (Oreochromis mossambicus) yang Direndam dengan Kulit Manggis (Garcinia mangostana L.) sebagai Pengawet Alami - Aulia Putri Nurmala; Hari Santoso; Ahmad Syauqi (Jurnal SAINS ALAMI (Known Nature), 2020)
Tilapia fish is one of the freshwater fish that is easily available in the market and is popular with the community. Freshwater fish are chosen as a source of protein, minerals, vitamins and fats for consumption. Purplish red mangosteen peels contain tannin, resin and compounds crystallizable mangostine (C2OH22O5), are easily soluble in alcohol or ether, and are insoluble in water. Tannin of mangosteen peel is a polyphenol compound and an additive functions as an antiseptic, a coloring agent for paint and ink. Compounds in mangosteen peel are able to bind proteins so that they can be used as natural preservatives, containing catechkin (flavan-3,4-diol), the proanthocyanidin group. The purpose of this study is to compare the effectiveness of mangosteen peel as a natural preservative in various concentrations in maintaining the quality of tilapia fish. The research method was carried out through experiments by soaking tilapia fish in mangosteen peel at a concentration of 0%, 25%, 50%, 75% for 24 hours with a temperature of 0-50C. Organoleptic analysis of changes in quality: gills, eyes, flesh texture and odor of tilapia fish (Oreochromis mossambicus) by measuring changes in pH of soaking water. The organoleptic test results showed that the highest organoleptic value was found at the highest concentration of 75%, with eye specifications having an organoleptic value of 8.3; gills have an organoleptic value of 8.6, odor has the highest organoleptic value of 8.7 and texture has an organoleptic value of 8.4. Soaking tilapia (Oreochromis mossambicus) carried out in the mangosteen peel (Garcinia mangostana L.) for 24 hours at 0-5OC showed the highest concentration of mangosteen peels had a lower pH (acidic) with the best organoleptic value.Keywords: Organoleptic, Mangosteen Skin Solution, pHABSTRAKIkan mujair salah satu ikan air tawar yang mudah didapat dipasar-pasar karena digemari masyarakat. Banyak  jenis ikan air tawar yang dapat dipilih sebagai sumber protein, karbohidrat, mineral, air, vitamin dan lemak untuk dikonsumsi. Kulit manggis berwarna merah keunguan karena mengandung tannin, resin, dan crystallizable mangostine (C2OH22O5), yang mudah larut dalam alkohol atau eter, dan tidak larut dalam air. Tanin merupakan senyawa polifenol, tanin kulit manggis sebagai zat aditif berfungsi sebagai antiseptik, bahan baku pewarna pada cat dan tinta. Kulit manggis mampu mengikat protein sehingga dapat digunakan sebagai bahan pengawet alami, mengandung katekkin (flavan-3,4-diol) golongan proantosianidin. Tujuan dari peelitian ini yaitu untuk membandingkan efektifitas kulit manggis sebagai bahan pengawet alami dalam berbagai konsentrasi dalam menjaga mutu ikan mujair, Untuk menganalisa perubahan mutu meliputi : insang, mata, tekstur daging dan bau (lisis) ikan mujair (Oreochromis mossambicus) yang direndam kulit Manggis (Garcinia mangostana L.). Untuk menganalisa perubahan pH rendaman dari kulit Manggis pada konsentrasi 0%, 25%, 50%, 75% selama 24 jam dengan suhu 0-50C. Penelitian ini merupakan penelitian eksperimen survey, dimana penelitian eksperimen yaitu dengan ikan mujair yang direndam dalam kulit manggis dengan konsentrasi 75%, 50%, 25% dan 0% selama 24 jam dalam suhu 0-50C. Survey dengan uji organoleptic. Perendaman ikan mujair (Oreochromis mossambicus) dalam kulit manggis (Garcinia mangostana L.) selama 24 jam dalam suhu 0-5OC didapatkan kesimpulan bahwa pada konsentrasi kulit manggis paling tinggi memiliki pH paling rendah (asam) dan nilai organoleptiknya yang paling baik.Kata kunci: Organoleptic, Larutan Kulit Manggis, pH